CBD promotes antitumor activity by modulating tumor immune microenvironment in HPV associated head and neck squamous cell carcinoma - Sen, Prakriti; Sadat, Sayed; Ebisumoto, Koji; Al-Msari, Riyam; Miyauchi, Sayuri; Roy, Souvick; Mohammadzadeh, Pardis; Lips, Kristin; Nakagawa, Takuya; Saddawi-Konefka, Robert; Sharabi, Andrew B.; Califano, Joseph A. (Frontiers in Immunology, 2025)
IntroductionMarijuana use is associated with HPV-positive head and neck squamous cell carcinoma (HNSCC). However, cannabinoid use continues to increase in the US general population for recreational purposes as well as in cancer patients for palliative care. In this study, we explored the role of cannabidiol (CBD) in promoting anti-tumor activity by modulating immune response in HPV-positive HNSCC by using pre-clinical models.MethodsThe anti-proliferative effect of CBD on HPV-positive HNSCC cells was evaluated through BrdU, apoptosis and migration analyses, followed by western blot analysis to assess its role in activating the MAPK pathway. Next, the anti-tumor immune response of CBD was evaluated in immunocompetent syngeneic mouse as well as in immune-deficient B6.129S7-Rag1tm1Mom/J or Rag 1 Knockout mice (Rag1 -/-) and athymic nude mouse. Immune cell infiltration was measured by flow cytometry, IHC and multiplex IHC analysis after subcutaneous injection of mEER cells. Furthermore, the anti-tumor activity of CBD on the tumor microenvironment was evaluated after the depletion of CD4+T cells and CD8+T cells in murine models.ResultsWe observed CBD treatment inhibited cell proliferation and migration by promoting apoptosis in HPV-positive HNSCC cells through activation of the MAPK pathway and its associated markers like ERK1/2, JNK/SAPK and MK2. CBD significantly inhibited tumor growth in immunocompetent mice but had no effect in immune-deficient models, indicating an immune-dependent mechanism. CBD enhanced infiltration of CD4+T and CD8+T cells, CD19+B cells, NK cells, and M1-like macrophages into the primary tumors of immunocompetent syngeneic mice models, implicating an enhanced anti-tumor immune response. Interestingly, we observed a significant increase in tumor volume in CD4-depleted mice treated with CBD as compared to CBD-treated wild-type mice suggesting the importance of CD4+T cells in CBD-mediated anti-tumor activity. Finally, multiplex IHC analysis demonstrated co-localization of CD4+T and CD8+ T cells with the activated MAPK marker phospho-p38 in CBD-treated tumors.DiscussionCBD inhibits tumor cell proliferation in HPV-positive HNSCC by activating the MAPK pathway. It also enhances anti-tumor activity by modulating the tumor immune microenvironment, promoting co-localization of p38 MAPK-activated CD4+ and CD8+ T cells.